2002
DOI: 10.1007/s000180200016
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced internalization and desensitization of the human nociceptin receptor expressed in CHO cells

Abstract: In this study, we examined agonist-induced internalization, recycling and signalling (measure of cAMP levels) of the cloned human nociceptin receptor (hNOP) expressed in CHO-K1 cells. Internalization was proven by a receptor-binding assay on viable cells. The agonist nociceptin/orphanin FQ (NC) promoted rapid internalization of the hNOP receptor (approximately 78% of cell surface receptors were lost after 2 min exposure to 1 microM NC) in a clathrin- and ATP-dependent manner. Internalization was more rapid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…The CCR7 GPCR, like the nociceptin GPCR demonstrates ligand-dependent differences in receptor internalization and desensitization (57)(58)(59)(60). Both GPCRs differentially regulate receptor fate following ligand binding (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCR7 GPCR, like the nociceptin GPCR demonstrates ligand-dependent differences in receptor internalization and desensitization (57)(58)(59)(60). Both GPCRs differentially regulate receptor fate following ligand binding (45).…”
Section: Discussionmentioning
confidence: 99%
“…2), the nociceptin receptor required different ligand-dependent incubation times to mediate receptor internalization. This may reflect the differential functions of the described ligands, since agonists and antagonists were internalized at different rates (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous groups have investigated the many stages of NOP receptor trafficking (for a thorough review, see Donica et al, 2013). Early work in the NOP receptor field had difficulty in finding agonistinduced internalization (Dautzenberg et al, 2001); however, later reports showed that NOP receptors indeed internalized in response to N/OFQ treatment (Spampinato et al, 2001(Spampinato et al, , 2002. Similar to the kappa opioid receptor disparities in internalization conditions , it is likely that differences reported in the internalization of NOP receptors are due to expression variability and model system used.…”
Section: B Nop Receptors and Kinase Signalingmentioning
confidence: 99%
“…NOP receptor recycling has not been extensively examined, although some groups have shown that, in transfected cells, once internalized receptors remain internalized after washout for up to 90 minutes to 2 hours in some reports (Spampinato et al, 2001;Spampinato et al, 2002). Long-term treatment of GPCRs with agonists generally causes them to either become recycled after some critical time window or to become transported to proteasomes and lysosomes.…”
Section: B Nop Receptors and Kinase Signalingmentioning
confidence: 99%
“…Clathrin-coated vesicles are trafficked to early endosomal compartments, where the receptor is completely internalized. Agonist-induced receptor internalization is (Cannarsa et al, 2012;Connor et al, 1996b;Donica et al, 2011;Mandyam et al, 2003;Thakker et al, 2007;Thakker and Standifer, 2002a,b) (Barnes et al, 2007;Bevan et al, 1998;Fukuda et al, 1998;Fukuda et al, 1997;Hashimoto et al, 2002;Hawes et al, 1998;Lou et al, 1997;McDonald et al, 2003;Okawa et al, 1999;Pan et al, 2002;Peluso et al, 2001;Spampinato and Baiula, 2006;Spampinato et al, 2002;Waits et al, 2004) COS-7 African green monkey kidney fibroblast-like cells transformed with SV40 ++++ G-protein coupling and NOP receptor expression (Chan and Wong, 2000;Chan et al, 1998;Ho et al, 2002 (Altier et al, 2006;Beedle et al, 2004;Evans et al, 2010) the intermediate phase of GPCR desensitization, where the receptor is now inaccessible for activation by the extracellular agonist, thereby inhibiting further agonist-mediated cellular responses. However, it is also an essential process for resensitization of receptors (Gainetdinov et al, 2004), as explained below.…”
Section: Homologous Nop Receptor Desensitizationmentioning
confidence: 99%